(untitled) (KIUT Publication, 2025)
Probiotics may be moderately effective in the treatment of periodontitis, especially when used in combination with conventional therapies such as professional cleaning and root planing. In oral health, probiotics have been shown to improve clinical indicators such as reduced pocket depth and decreased bleeding on probing. While the use of probiotics as an adjunct to non-surgical periodontitis therapy has demonstrated promising outcomes in clinical and microbiological parameters over time, addressing the complexities associated with probiotic interventions in periodontitis requires a multifaceted approach.